Investigating the Properties of the Vertisols at Kenana III and IV Towards Enhancing Management Practices (Sennar State - Sudan) - M. Ali, El Abbas Doka; Aitken, John; Munro, Neil R. (European Journal of Applied Sciences, 2017)
A series of studies were initiated in Sudan in the early 1950s for utilization of the Nile Waters [19]. On the basis of these studies the Rosaries Dam was built on the Blue Nile. By the end of 2008 a programme to start the heightening of the dam was started with outlets for canals on both banks. At the same time further agricultural development on two irrigation projects, the Kenana and Rahad II commenced with soil surveys and irrigation design. The Kenana Area lies between the Blue Nile and the White Nile and runs south east to North West from Disa to Managil. Kenana Area is almost flat with predominantly clayey soils [21], [17]. Kenana III lies midway between the Blue Nile and the White Nile south of Sennar-Kosti railway line. Kenana IV area finally lies to the north west of Kenana III area. The soil study area is partly semi-arid and partly arid, and experiences slight rainfall in the order of 350 mm in its northern edge, increasing to some 650 mm at its southern boundary near Jebel Dali. The soil surveys carried in the area were made at semi-detailed level and the key specifications are a field density of 1 observation each 100 ha and map scales of 1:50,000 and 1:100,000. Previously published soil survey information was reviewed and incorporated in these surveys. In these surveys a number of potential agricultural options in terms of adapted cropping patterns, systems of management and two methods of surface and pressure irrigation were considered for development [6]. The most dominant soils are the Vertisols which have high potential for crop production, but some constraints emerge affecting crop performance and decreasing yields. Those limitations are aspects of land degradation, manifested in deterioration of physical and chemical properties. Continuous cropping of Vertisols, through time, leads to compaction and eventually develops hardpan at the subsurface, reducing porosity, intensity of cracking and obliterating water movement. Such adverse effects are indicators of degraded soil physical properties. To minimize the concurrence of those hazards management procedures should adhere to land and crop management systems. Parallel to this approach, the fertility status is likely to decline due to intensive farming of some nutrient-depleting crops, but this nutrient deficiency is correctable through implementing a fertilizer programme. In the study area, some parameters are management-factors determining e.g. flat slope favouring uniform distribution of irrigation water through well designed irrigation and drainage network, and sub-soiling preparing proper seedbed. Those technical inputs if properly used and practiced they are expected to sustain crop production. Keywords: Vertisols, Kenana Area, Irrigated Agriculture; Soil survey; Landsat, Clay plain